Evaluation of hand hygiene compliance rates of five years in critical care unit of a tertiary hospital in Nepal - Joshi, Shirish Raj; Dangol, Reshma; Dangol, Laxmi; Rana, Roshani; Khanal, Sushil; Acharya, Subhash Prasad (Grande Medical Journal, 2021)
Introduction: Hand hygiene (HH) has been proven as the most effective measure in controlling healthcare associated infections. However, HH compliance rates among health care workers in hospitals are often significantly low. There are no studies to address HH compliance and interventions to increase compliance in Nepal. We aimed to evaluate the compliance of hand hygiene in critical care setting in a tertiary care center in Nepal. Methods: This is a descriptive cross-sectional study conducted from 1st January 2016 to 31st December 2021 among nurses and physicians working in critical care units of Grande International Hospital in Kathmandu. Data regarding the compliance to hand hygiene were collected. The rate missed opportunities among ‘My five moments of hand hygiene’ were also studied. Data was entered and analyzed in Microsoft Excel. Point estimate at 99% confidence interval was calculated along with frequency and percentage for binary data along with mean and standard deviation for continuous data. Results: Out of 4908 hand hygiene opportunities observed, compliance rate was found to be 66% (64.26 - 67.74 at 99% Confidence Interval). Among different health care personnel working in Intensive Care Unit, consultant physicians were found to have highest compliance rate followed by nursing staff. Conclusions: Systematically structured hand hygiene strategy along with education programs, continuous monitoring and evaluation, feedback and team approach could result in increased compliance rate but continuous effort is needed to sustain this improvement.